ABNORMAL REGULATION OF MICROVASCULAR TONE IN A MURINE MODEL OF SICKLE CELL DISEASE ASSESSED BY CONTRAST ULTRASOUND - Wu, Melinda D. (J Am Soc Echocardiogr, 2015)
BACKGROUND: Microvascular dysregulation, abnormal rheology, and vaso-occlusive events play a role in the pathophysiology of sickle cell disease (SCD). We hypothesized that abnormalities in skeletal muscle perfusion in a murine model of SCD could be parametrically assessed by quantitative contrast-enhanced ultrasound (CEU) perfusion imaging. METHODS: We studied a murine model of moderate SCD without anemia produced by homozygous β-globin deletion replaced by human βs-globin transgene (NY1DD−/−, n=18), heterozygous transgene replacement (NY1DD+/−, n=19), and C57Bl/6 control mice (n=14). Quantitative CEU of the proximal hindlimb skeletal muscle was performed at rest and during contractile exercise (2 Hz). Time-intensity data were analyzed to measure microvascular blood volume (MBV), microvascular blood transit rate (β), and microvascular blood flow (MBF). Erythrocyte deformability was measured by elongation at various rotational shears. RESULTS: At rest, muscle MBV was similar between strains whereas β was significantly (ANOVA p=0.0015) reduced to a similar degree in NY1DD−/− and NY1DD+/− compared to wild-type mice (0.24±0.10, 0.16±0.07, and 0.34±0.14 s(−1), respectively), resulting in a reduction in MBF. During contractile exercise, there were no group-wise differences in β (1.43±0.67 s(−1), 1.09±0.42 s(−1), 1.36±0.49 s(−1); for NY1DD−/−, NY1DD+/−, and wild-type, respectively), nor for MBF or MBV. Erythrocyte deformability at high shear stress (≥5 Pa) was mildly reduced in both transgenic groups, although it did not correlate with the blood flow or β. CONCLUSIONS: CEU in skeletal muscle has revealed a lower microvascular blood transit rate in the NY1DD model of SCD and sickle trait but no alterations in MBV. The abnormality in microvascular blood transit rate is likely due to vasomotor dysfunction since it abrogated by contractile exercise and at rest is only weakly related to erythrocyte deformability.